Effects of busy mindset on preference for high-calorie foods - Ai, Yijie; Jiang, Min (Scientific reports, 2024)
More people feel busier than ever. Recognising busyness as an environmental factor that influences food preferences is essential when considering health-related decisions. This research investigates how the subjective perception of busyness—which is referred to as a busy mindset—affects consumers’ food preferences via two studies. Study 1 was a laboratory experiment conducted using a manipulation method with 135 undergraduate student participants. Study 2 used an online self-report questionnaire to repeat the findings of Study 1 and including 209 social participants. The results from the two studies showed that a busy mindset induced individuals to prefer high-calorie foods, and energy expenditure efficiency mediated this effect. Moreover, the subjective perception of busyness increased individuals’ estimated need for calories and induced them to prefer high-calorie foods over high-nutrition or hedonic foods. These findings suggest that food preferences in the busy mindset have potential implications for individuals’ food consumption.